Standardized Methodology of Scaffold-Free and Scaffold-Based 3D Epithelial Spheroid Culture for Skin Regenerative Research - Ramos-Pinto, Mariana B.; de Almeida Lança, Maria Leticia [UNESP]; Squarize, Cristiane H.; Castilho, Rogerio M. (MDPI, 2025)
Background: Extensive skin injuries from severe burns or chronic non-healing ulcers overwhelm the body's natural repair mechanisms, while current therapeutic approaches relying on autologous skin grafting are limited by donor site availability. Three-dimensional epithelial spheroid cultures enhance stem cell regenerative potential, but standardized comparative methodologies are lacking. Methods: We established a comprehensive framework comparing scaffold-free and scaffold-based epithelial spheroid systems using HaCaT keratinocytes. High-throughput approaches utilized BioFloat and ELPLASIA 96-well platforms, while low-throughput 6-well ULA plates generated heterogeneous populations (holospheres, merospheres, paraspheres). Scaffold-based studies embedded spheroids in Matrigel to evaluate outgrowth capacity. ROCK1 inhibitor treatment was assessed for stemness enhancement. Results: High-throughput systems generated uniform spheroids with high reproducibility and consistent circularity. Low-throughput cultures produced heterogeneous populations with distinct size distributions (holospheres: 408.7 μm2, merospheres: 99 μm2, paraspheres: 14.1 μm2). In Matrigel scaffolds, merospheres and paraspheres migrated outward, forming epithelial sheets, while holospheres remained intact as BMI-1+ stem cell reservoirs. ROCK1 inhibition enhanced holosphere formation, preserved stemness markers, and reduced premature differentiation. Conclusions: This standardized toolbox demonstrates scaffold-free systems optimize scalability for screening while scaffold-based approaches enable physiologically relevant regenerative studies. Integration of both methodologies provides flexibility matching experimental design to scientific objectives, accelerating translation to clinical applications.